The law of finders keepers - Turnage, Sheila (Turnage, Sheila. Mo & Dale mystery., 2018)
"A rumor that Blackbeard's buried treasure is somewhere near Tupelo Landing causes pirate fever to sweep through town just as clues about Mo's Upstream Mother surface and the Desperado Detectives--aka Mo LoBeau and her best friends Dale and Harm--take on the most important case of Mo's life"--